Pisuke In The Marriage Customs Of The Sasak Tribe From The Perspective Of ‘Urf: A Case Study In Terara Village East Lombok - Muh Hamdani; Saini (Al-Hikmah: International Journal of Islamic Studies, 2025)
The pisuke tradition represents a distinctive practice in the marriage customs of the Sasak ethnic community in East Lombok. It appears during the nyelabar stage as a form of offering from the groom’s family to the bride’s family. While culturally regarded as a symbol of respect and social responsibility, the practice of pisuke has sparked debate within Islamic law, as it is often perceived as resembling a transactional exchange between the two families. This study aims to describe the form and meaning of pisuke within Sasak society and to examine its legal status based on the theory of ‘urf in uṣūl al-fiqh. The research employs a qualitative approach using a case study method conducted in Terara Village, Terara District, East Lombok Regency. Data were collected through in-depth interviews, field observations, and documentation of local marriage ceremonies. The findings reveal that pisuke constitutes ‘urf fi‘liy (customary practice expressed through actions) and ‘urf ‘amm (a widely accepted communal custom). However, from the perspective of Islamic law, it may be classified as ‘urf ṣaḥīḥ when performed voluntarily as an expression of respect, yet becomes ‘urf fāsid when accompanied by coercion, imposed as a condition of the marriage contract, or financially burdensome to one party. It is concluded that pisuke may be preserved as a cultural tradition provided it does not contradict the principles of al-riḍā (mutual consent), al-‘adl (justice), and the objectives of maqāṣid al-sharī‘ah, namely to uphold fairness, dignity, and the welfare inherent in Islamic marriage.